2000
DOI: 10.1128/cdli.7.1.45-48.2000
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Weck-Cel Collection Method for Quantitation of Cytokines in Mucosal Secretions

Abstract: Measurement of immune components in mucosal secretions is important for the evaluation of local immunity at the mucosal surfaces. The Weck-Cel ophthalmic sponge provides a method for the collection of these secretions. The sponge absorbs a relatively large volume of material, therefore allowing for quantitation of multiple immune components. Additionally, it provides a method in which the same device may be used to collect specimens from different mucosal sites, such as the genital tract and oral cavity. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 8 publications
1
43
0
1
Order By: Relevance
“…In in vitro experiments, we confirmed that IL-4 and IFN-␥ may be poorly recovered from Weck-Cel ophthalmic sponges (16) and demonstrated that immune markers may be more reliably recovered from in vitro-loaded Ultracell and Merocel ophthalmic sponges. In particular, recovery from Merocel sponges, which are composed of hydroxylated polyvinyl acetate, was nearly 100% for all tested cytokines in the in vitroloading experiment, except for IL-6, whose levels of recovery were equally poor from all sponges.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In in vitro experiments, we confirmed that IL-4 and IFN-␥ may be poorly recovered from Weck-Cel ophthalmic sponges (16) and demonstrated that immune markers may be more reliably recovered from in vitro-loaded Ultracell and Merocel ophthalmic sponges. In particular, recovery from Merocel sponges, which are composed of hydroxylated polyvinyl acetate, was nearly 100% for all tested cytokines in the in vitroloading experiment, except for IL-6, whose levels of recovery were equally poor from all sponges.…”
Section: Discussionsupporting
confidence: 54%
“…Sponges were extracted according to a previously described protocol (16). Briefly, each sponge was weighed to estimate the volume of secretions absorbed onto the sponge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the protein extraction protocol described [12]. Briefly, the sponges were equilibrated in 300 l of extraction buffer consisting of PBS (pH 7.0), 0.25M NaCl and 10% fetal calf serum, for 30 min at 4°C.…”
Section: Protein Extraction From Weck-celmentioning
confidence: 99%
“…Cervical secretions were obtained with a syringe, whereas vaginal fluids were collected with Weck-cel sponges. Cervical secretions are not regarded as ideal specimens for assessment of genital immune responses in large-scale immunization studies, since the collection is timeconsuming, requires gynecological assistance, and at times yields small amounts of secretions (9,28). Vaginal fluid, on the other hand, is an easily accessible secretion.…”
Section: Discussionmentioning
confidence: 99%